John Selden : Measures of the Holy Commonwealth in Seventeenth-Century England - Barbour, Reid (Book collections on Project MUSE., 2003)
John Selden: Measures of the Holy Commonwealth in Seventeenth-Century England is the first text in over a century to examine the whole of Selden's works and thought. Reid Barbour brings a new perspective to Selden studies by stressing Selden's strong commitment to a 'religious society,' by taking a closer and more sustained look at his poetic interests, and by systematically examining his Latin publications (particularly those using Jewish sources).Offering critical close readings of Selden's oeuvre, Barbour posits that the overriding aim of Selden's career was to bolster religious society in the face of its imminent demise. He argues that Selden's scholarly career was committed to resolving an essentially religious question about how best to establish the holy commonwealth in both lawfulness and spiritual abundance.Perhaps the greatest strength of Barbour's analysis emerges from his overall interpretation of Selden's corpus within the context of what the author calls a "religious society"; this approach emphasizes the religious commitments of Selden and subverts earlier readings of him as a cynical, skeptical, secular thinker who attacked, rather than upheld, a Judeo-Christian model of society. Engaging in style and substantive in analysis, Barbour's John Selden will add considerably to the limited body of work on this important seventeenth-century savant.